2010
DOI: 10.5101/nbe.v2i1.p45-55
|View full text |Cite
|
Sign up to set email alerts
|

Real time PCR based on Fluorescent Quenching of Mercaptoacetic Acid-Modified CdTe Quantum Dots for Ultrasensitive Specific Detection of Nucleic Acids

Abstract: A ultra-sensitive, highly specific, real-time polymerase chain reaction system based on mercaptoacetic acid-modified CdTe nanocrystals(mQDs) is reported. With the addition of 3 nm mQDs into the PCR reagent, the photoluminescent(PL) intensities of mQDs decreased gradually as the DNA templates and PCR cycles increased, in an approximate negative linear relation to the DNA concentration logarithm or cycles, the PL peaks exhibited red-shifts synchronously. Mg 2+ ions decreased the PL intensity of mQDs in a dose-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…They proposed a hypothesis for PCR enhancement in which GNFs can improve heat dissipation in PCR, which leads to more rapid DNA denaturation during the denaturation stage; then the van der Waals forces among NPs may contribute to binding with PCR reagents for enhanced interaction during the second stage; at last, the third stage might have been improved again because of good dissipation of heat, finally resulting in the improvement of PCR products. In addition, Cui et al , also suggested a similar enhancement mechanism for NPs in which the thermal entropy of the NPs is in favor of dynamic contact among PCR elements and reduces the mispairing between primers and templates at the each step during the PCR process. Thus, a high-GC-content PCR system should be an ideal template to study the heat transfer effect of nanomaterials.…”
Section: Resultsmentioning
confidence: 99%
“…They proposed a hypothesis for PCR enhancement in which GNFs can improve heat dissipation in PCR, which leads to more rapid DNA denaturation during the denaturation stage; then the van der Waals forces among NPs may contribute to binding with PCR reagents for enhanced interaction during the second stage; at last, the third stage might have been improved again because of good dissipation of heat, finally resulting in the improvement of PCR products. In addition, Cui et al , also suggested a similar enhancement mechanism for NPs in which the thermal entropy of the NPs is in favor of dynamic contact among PCR elements and reduces the mispairing between primers and templates at the each step during the PCR process. Thus, a high-GC-content PCR system should be an ideal template to study the heat transfer effect of nanomaterials.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, different QD–oligonucleotide probe conjugates are needed for different target sequences (poor universality). The only exception was the work reported by Cui and co-workers that mercaptoacetic acid-modified CdTe QDs could achieve real-time monitoring of PCR, but the underlying mechanism was not clear …”
Section: Introductionmentioning
confidence: 99%
“…It should be pointed out that these two assay platforms involved postamplification open-tube addition of the detection probes (including the QD-based probes) attributed to incompatibility issue, which not only increased the risk of carryover contamination but also increased the assay time. On the other hand, a few closed-tube/one-step QD-based PCR platforms have been reported. Wang and co-workers and Pang and co-workers demonstrated that oligonucleotides/primers bound to QDs were successfully extended in the presence of specific complementary target sequences during PCR. Despite the excellent detection performance of QD–oligonucleotide probe conjugates, their preparation is costly (oligonucleotide with attachment functional group; typically prepared via ligand exchange with thiol-modified oligonucleotide).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique has great potential as a practical clinical tool for medical diagnosis. As part of the preliminary effort to establish a prewarning data library of early gastric cancer based on biological microarrays and CAD technology [11,12], we have been screening and cloning differentially expressed genes between precancerous lesion and gastric cancer, and also designed and prepared nanoprobes to find early in situ gastric cancer, with the aim of establishing a gastric cancer prewarning system [13][14][15][16][17][18][19][20][21][22]. The present study is a coherent part of our overall activities on molecular mechanism of gastric diseases including gastritis, precancerous lesion and carcinoma.…”
Section: Introductionmentioning
confidence: 99%